A comparative evaluation of the antimicrobial efficacy of Chlorhexidine and Chlorine dioxide on self-ligating brackets contaminated with Streptococcus mutans biofilm- An In vitro study - Ashish Kumar Singh; Yash Salkar; Puneet Batra; Garima Arora; Shakila Mahesh (Elsevier, 2024)
Objective: To evaluate and compare antimicrobial efficacy of Chlorhexidine and Chlorine dioxide mouthwashes on S.mutans biofilm created on metal and ceramic self-ligating brackets. Materials and methods: A total of 162 metal and ceramic self-ligating brackets (3M™ SmartClip™ & Clarity SL™) were randomly divided into 3 groups and 2 subgroups. Standard procedures were followed to coat all brackets with S.mutans biofilm. The biofilms were cultivated which were then subjected to the effects of the mouthwashes. Quantitative assessment was carried out by comparing the number of viable colonies of S.mutans. A Mann-Whitney U test was used to compare the data between the experimental and control groups. (p < 0.05). Result: When compared to untreated controls the antimicrobial efficacy of Chlorhexidine Digluconate and Chlorine Dioxide mouthwashes was found to be statistically significant (p = 0.00). The comparison between Chlorhexidine digluconate and Chlorine dioxide mouthwashes was not statistically significant in Ceramic self-ligating group (p = 0.502) and statistically significant in Metal self-ligating group (p = 0.001) Conclusion: S mutans colonies on metal and ceramic self-ligating brackets can be reduced effectively by Chlorhexidine digluconate and Chlorine dioxide mouthwashes. Chlorhexidine digluconate more effective for metal bracket group. Both mouthwashes had comparable antimicrobial effectiveness, with the difference in the number of viable colonies following exposure for ceramic bracket groups.